Effects of sulfur oxyanions and magnetite on the corrosion behavior of alloy 600 under simulated PWR secondary water conditions - Jeoh Han; Do Haeng Hur; Geun Dong Song; Soon-Hyeok Jeon (Journal of Materials Research and Technology)
This study investigates the corrosion behavior of Alloy 600 in sulfur oxyanions (sulfate and tetrathionate) solutions. The corrosion rate and oxide thickness of Alloy 600 drastically increase by the presence of sulfur oxyanions in the environment. The phenomenon is mainly caused by tetrathionate ions, not sulfate ions. When Alloy 600 and magnetite are electrically connected in the solutions, they respectively behave as an anode and a cathode. This galvanic coupling effect further accelerates the corrosion of Alloy 600. The preferential dissolution of Ni and reduction of tetrathionate result in the formation of an oxide layer composed of Ni-depleted Cr–Fe oxides and Ni3S2 compounds.